1998
DOI: 10.1177/002215549804600704
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Monoclonal Antibodies Specific to the Serotonin 5-HT2AReceptor

Abstract: SUMMARY Serotonin (5-hydroxytryptamine, 5-HT) mediates many functions of the central and peripheral nervous systems by its interaction with specific neuronal and glial receptors. Fourteen serotonin receptors belonging to seven families have been identified through physiological, pharmacological, and molecular cloning studies. Monoclonal antibodies (MAbs) specific for each of these receptor subtypes are needed to characterize their expression, distribution, and function in embryonic, adult, and pathological tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 69 publications
6
38
1
Order By: Relevance
“…Radioligand binding demonstrated specific binding of [ 3 H]ketanserin, and this was estimated as approximately 34 fmol/mg protein. Antibodies specific for the 5-HT 2A receptor detected a protein doublet at around 55 kDa, which was consistent with the predicted molecular mass of the 5-HT 2A receptor (53 kDa) and with previous reports (Wu et al, 1998). Immunohistochemistry localized this receptor to the smooth muscle cells of the myometrium, although not all muscle cells were labeled.…”
Section: Discussionsupporting
confidence: 91%
“…Radioligand binding demonstrated specific binding of [ 3 H]ketanserin, and this was estimated as approximately 34 fmol/mg protein. Antibodies specific for the 5-HT 2A receptor detected a protein doublet at around 55 kDa, which was consistent with the predicted molecular mass of the 5-HT 2A receptor (53 kDa) and with previous reports (Wu et al, 1998). Immunohistochemistry localized this receptor to the smooth muscle cells of the myometrium, although not all muscle cells were labeled.…”
Section: Discussionsupporting
confidence: 91%
“…Western blots probed with the anti-5-HT 2A R antibody detected an immunoreactive band of about 55 kDa in both the wild-type and mutant receptor-expressing cells (Fig. 5: A and B), as reported earlier for this antibody in NIH-3T3 cells (15), suggesting that the mutations in TMH 3 did not cause any abnormality in the receptor proteins. It is also suggested that the mutant proteins are inactive but are still expressed and detectable by antibody.…”
Section: Western Blot Analysissupporting
confidence: 84%
“…The monoclonal antibody to 5-HT 2A R (clone G186-117; BD Pharmingen # 556326) was raised against a recombinant fusion protein of glutathione S-transferase and a peptide containing amino acids 1-76 of the human 5-HT 2A R receptor (Wu et al, 1998), although a recent report indicates that the targeted epitope is comprised of a sequence between amino acids 64-71 (Cornea-HĂ©bert et al, 2002). The specificity of the antibody was determined in Western blot analyses; it labeled a single band of 55 kDa.…”
Section: Antibody Specificitymentioning
confidence: 99%
“…The specificity of the antibody was determined in Western blot analyses; it labeled a single band of 55 kDa. Staining was completely eliminated by preadsorption of the antibody with the GST-5HT 2A R fusion protein (200 g protein/100g antibody), but not with GST-5HT 2B R or GST-5HT 2C R fusion proteins (Wu et al, 1998).…”
Section: Antibody Specificitymentioning
confidence: 99%